Hindī sāhitya kā itihāsa - Śukla, Rāmacandra (Lokabhāratī Prakāśana, 2012)
On the writings of Ram Chandra Shukla, 1884-1941, Hindi author, and history of Hindi literature of the 20th century.
In Devanagari-Schr., Hindi
Keywords: Shukla; Ram Chandra <1884-1941>; Śukla; Rāmacandra; Hindi literature; Geschichte; Hindi; Literatur